One-pot synthesis of colloidal silicon quantum dots and surface functionalization via thiol-ene click chemistry - Cheng, X.; Gondosiswanto, R.; Ciampi, Simone; Reece, P.; Gooding, J. (The Royal Society of Chemistry, 2012)
A solution method for preparing surface functionalized colloidal silicon quantum dots (SiQDs) is presented. SiQDs prepared by this method are reasonably monodispersed and can be further functionalized via thiol–ene click reactions to introduce specific functionalities (i.e. –NH2, –COOH, –SO3−, alkane, alkene).